Criminal Sentence Disparity of Village Funds Abuse In Maluku - Corputty, Patrick; Pasalbessy, John Dirk; Hattu, Jacob; Salamor, Yonna Beatrix (SASI, 2023)
Introduction: Difference or disparity in sentencing is one of the important topics in criminal law. The disparity in sentencing means that there are differences in the amount of punishment handed down by the court in cases that have the same characteristics.Purposes of the Research: The purpose of this study is to find out why there is a disparity in criminal penalties in court verdicts in cases of corruption in the misuse of village funds in Maluku.Methods of the Research: This study uses a normative juridical method.Results of the Research: Based on the results of the study, essentially the disparity in imposing criminal penalties in court verdicts on corruption cases of misuse of village funds is due to strafmaat (criminal threats) for different perpetrators.